Interventions for addressing trauma among people with HIV: a narrative review. Issue 4 (3rd April 2022) - Goldhammer, Hilary; Marc, Linda G.; Chavis, Nicole S.; Psihopaidas, Demetrios; Massaquoi, Massah; Cahill, Sean; Nortrup, Erin; Dawson Rose, Carol; Meyers, Janet; Mayer, Kenneth H.; Cohen, Stacy M.; Keuroghlian, Alex S.
ABSTRACT: Traumatic experiences are disproportionately prevalent among people with HIV and adversely affect HIV-related health outcomes. As part of a national cooperative agreement funded by the Health Resources and Services Administration's HIV/AIDS Bureau, we searched the literature for interventions designed to address trauma among people with HIV in the U.S. Our search yielded 22 articles on 14 studies that fell into five intervention categories: expressive writing, prolonged exposure therapy, coping skills, cognitive–behavioral approaches integrated with other methods, and trauma-informed care. Thematic elements among the interventions included adaptating existing interventions for subpopulations with a high burden of trauma and HIV, such as transgender women and racial/ethnic minorities; addressing comorbid substance use disorders; and implementing organization-wide trauma-informed care approaches. Few studies measured the effect of the interventions on HIV-related health outcomes. To address the intersecting epidemics of HIV and trauma, it is critical to continue developing, piloting, and evaluating trauma interventions for people with HIV, with the goal of wide-scale replication of effective interventions in HIV settings.